COST EFFECTIVENESS ANALYSES MODELS IN THE DEFENCE SYSTEM IN BULGARIA - Terziev, Venelin; Dimitrova, Sevdalina (European Scientific Journal, ESJ, 2014)
The thesis resulting from the research on the â€žcosts - effectsâ€ relation is the principle of economic efficiency of defence capabilities. At first glance, the arguments in this direction are well-known and popular in crisis situations of various nature, including the current financial and economic crisis in the country, the question about the cost of public welfare - security and defence is debatable. This cost is manifested through the defence capabilities of a country. In the new security environment the compilation of a National Defence Strategy is a priority of the Defence Ministry, which has more and more limited resources. This means that they should be treated as an economic activity. An economic activity is considered "any purposeful activity, allocating and combining scarce resources among alternatives, making it possible to maximize the outcomes and minimize costs." The ratio between the costs and benefits of a given resource or combination of resources to achieve a pre -defined objective is pushed to the forefront and the rationalization of management decisions is based on it. This necessitates a cost effectiveness analysis hence the evaluation of the outcomes (benefits) is manifested in the â€žcost - effect (benefit)â€ analyses.